The Boundaries of the Human: The Relationship Between Natural, Cultural, and Artificial - D'Alessandro, Simone (Italian Sociological Review, 2025)
What constitutes the ‘absolutely other’ for the human being in relational terms? How do nature and culture relate to the human being and orientate his constitution? Are there insurmountable limits that distinguish humans from the natural and artificial non-human? Starting with these research questions, we will trace theories and paradigms in the sociological and anthropological fields that from the 19th century to the present have generated and constructed fractured relationships - the result of dualist, stereotyped, and conflictual interpretations - between natural, cultural, and artificial. Continuing the analysis from a comparative perspective, contradictions and unanswered questions will be highlighted.